Digital Politeness: A Gendered Analysis of Complimenting Behaviour on Social Media - Laabidi, Abdelfattah; LAACHIR, Abdelouahed; Infi, Ouidad (International Journal of Language and Literary Studies, 2025)
With the rapid advancement of technology and the excessive use of social media as platforms for communication, the shades of digital politeness and complimenting speech acts have become a worthy study area. This paper examines the overlap between digital communication, gender, and complimenting behaviour in online communication. It mainly sheds light on how men and women differ in using, reacting and interpreting compliments in online interactions. The current study adopts a quantitative approach by mixing descriptive and inferential statistics. Data are collected using a discourse completion test that comprises seven distinctive scenarios with different power, distance and ranking position relationships. The participants are 62 students from ENS, Moulay Ismail University. After running a Pearson Chi-squared test for each scenario in the DCT, the findings reveal a strong correlation between gender and the choice of complimenting strategies, claiming that gender is an impactful variable affecting compliments' making and interpretation in online contexts. It also concluded that the differences between male and female language users lie in the excessive use of additional cues by female speakers to express emotions, like emojis, liking, tagging and sharing. This study can eventually deepen and enhance the debate on politeness in online dyads by highlighting the intricacies of gendered compliments speech acts. It affords a foundation for further research into pragmatic competence in online contexts.